(untitled) (Annals of Medical Research, 2022)
Aim and Background A melatonin receptor agonist Ramelteon is a drug that is also used in urinary tract infections. Melatonin is known to have an effect on smooth muscle contraction. In this study, we aimed to question whether ramelteon exerts a melatonin-like effect on bladder contractions. Material Methods Wistar-albino (n = 8) intact female rats were used in the study. After decapitation, 1.5x5 mm bladder strips were examined in an isolated organ bath in which there was Krebs-Henseleit solution. After the regulation period, ramelteon was applied non-cumulatively in two separate doses of 0.2μM, 1μM. The area under the curve (AUC) and peak to peak (p-p) values ​​before and after the application were normalized as% change. Results Exposure of bladder strips to ramelteon significantly increased contractions. Ramelteon caused a statistically significant increase in p-p, AUC values ​​of spontaneous bladder contractions at a dose of 0.2 and 1μM (P <0.05). Conclusion Ramelteon has an activator effect on spontaneous bladder contractions unlike melatonin. The physiopathological mechanisms under activator activity need to be investigated with further studies. This effect should be taken into account in clinical use.